Bioinspired Depletion‐Resistant Lubricant‐Infused Surfaces with Self‐Replenishing Lubrication Through Capillary Filament. Issue 16 (27th July 2021) - Li, Jiaqian; Zhao, Haibo; Wang, Liqiu
Abstract: Lubricant‐infused nanostructured surfaces have emerged as a type of multifunctional coatings with exceptional advantages of super liquid‐repellency, low contact angle hysteresis, and self‐healing. However, due to their low oil storage trapped by nanostructures, such type of functional surfaces is susceptible to the depletion of lubricant fluids especially under extreme conditions. In this study, an earthworm‐inspired hierarchical lubricant‐infused surface with superior self‐replenishing lubrication but without the input of external stimulus is developed. The top nanostructured membrane acts as a skin to stabilize the slippery oil layer, while the bottom square microwells work as reservoirs to store sufficient lubricant oil and replenish the nanofilm analogous to the earthworm grands. Through the seamless collaboration of capillary corner filament inside the microwell and wettability gradient between the microwell and the nanofilm, the lubricant stored in the microwells can be directionally and timely transported for replenishing the nanofilm when the lubricant within the nanofilm is depleted. Compared with the conventional nanostructured lubricant‐infused surfaces, the surface can promise a long‐term superior lubricating action under extreme conditions of cooling, heating, and continuous droplet impinging. It is envisioned that the designed self‐replenishing lubricant‐infused surface can be useful in applications that involve extreme environments. Abstract : An earthworm‐inspired lubricant‐infused surface with superior self‐replenishing lubrication is developed. The bottom microwells work as reservoirs to store sufficient lubricant oil and replenish the top nanofilm through capillary corner filament inside the microwell and wettability gradient between the microwell and the nanofilm. Such surface promises a long‐term lubricating action under extreme conditions of cooling, heating, and continuous droplet impinging.